2010
DOI: 10.1289/ehp.0901376
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Environmental Phthalate Exposure and the Intelligence of School-Age Children

Abstract: BackgroundConcern over phthalates has emerged because of their potential toxicity to humans.ObjectiveWe investigated the relationship between the urinary concentrations of phthalate metabolites and children’s intellectual functioning.MethodsThis study enrolled 667 children at nine elementary schools in five South Korean cities. A cross-sectional examination of urine phthalate concentrations was performed, and scores on neuropsychological tests were obtained from both the children and their mothers.ResultsWe me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(142 citation statements)
references
References 54 publications
(66 reference statements)
6
132
3
1
Order By: Relevance
“…This assumption was based on the fact that many patients were admitted after exposure to extracorporeal circuits for surgery [19] and on the number of indwelling medical devices that typically diminishes throughout PICU stay, taking into account the half-life of the metabolites (between 5-15h) [20]. The available evidence suggests that both the concentration of circulating DEHP metabolites to which the brain is exposed and the duration of this exposure determine any eventual long-term neurocognitive harm [21,22] within a concept of "threshold" toxicity [23]. Therefore, we decided to consider the product of the last day plasma concentration and the duration of PICU stay as that exposure to circulating phthalates during PICU stay that was minimally present for each patient, further referred to as the phthalate "exposure".…”
Section: Emethods 4 Bootstrap Selection Of Significant and Stable Pomentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption was based on the fact that many patients were admitted after exposure to extracorporeal circuits for surgery [19] and on the number of indwelling medical devices that typically diminishes throughout PICU stay, taking into account the half-life of the metabolites (between 5-15h) [20]. The available evidence suggests that both the concentration of circulating DEHP metabolites to which the brain is exposed and the duration of this exposure determine any eventual long-term neurocognitive harm [21,22] within a concept of "threshold" toxicity [23]. Therefore, we decided to consider the product of the last day plasma concentration and the duration of PICU stay as that exposure to circulating phthalates during PICU stay that was minimally present for each patient, further referred to as the phthalate "exposure".…”
Section: Emethods 4 Bootstrap Selection Of Significant and Stable Pomentioning
confidence: 99%
“…In vitro studies, animal studies and observational reports in humans suggest that chronic exposure to DEHP may deleteriously affect neurocognitive development [19][20][21][22][23]. Specifically, a toxic effect on dopaminergic neurons was suggested to contribute to an increased incidence of attention-deficit disorders in young children exposed to environmental phthalates [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Another study performed in South Korea among 667 elementary schools children evaluated a relationship between the urine concentrations of the metabolites of DEHP and DBP and children's vocabulary scores. Among boys, but not girls, a negative association was found between increasing MEHP phthalate concentrations and the sum of DEHP metabolite levels and vocabulary score [59]. The association of prenatal phthalate exposure with behavior and executive functioning at 4-9 years of age was examined in multiethnic prenatal population in New York City.…”
Section: Thyroid Function In Childrenmentioning
confidence: 99%
“…Animal studies have also revealed that the phthalate might cause hyperactivity similar to the clinical syndrome of attention-deficit/hyperactivity disorder (ADHD) found in children [56]. Exposures to phthalates have been examined in relation to neurodevelopment among neonates 5 days after birth in United States [57], in Korea in children from elementary schools [58,59] and in United States both among children 4-9 years [60] and 3.6-6.4 years of age [61] (Table 4). …”
Section: Children's Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation